2003
DOI: 10.1086/367858
|View full text |Cite
|
Sign up to set email alerts
|

Hajj‐Associated Outbreak Strain ofNeisseria meningitidisSerogroup W135: Estimates of the Attack Rate in a Defined Population and the Risk of Invasive Disease Developing in Carriers

Abstract: An outbreak of disease due to Neisseria meningitidis serogroup W135 (W135) occurred in 2000 and 2001 among pilgrims returning from the annual Islamic pilgrimage to Saudi Arabia (the Hajj) and in their contacts. For the Hajj in 2000, the attack rate of W135 disease was 25 cases per 100,000 pilgrims. After the introduction of quadrivalent meningococcal vaccine for the Hajj in 2001, no pilgrim developed W135 disease. The estimated attack rates for household contacts of returning pilgrims were 18 cases and 28 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 23 publications
1
77
0
Order By: Relevance
“…Further, no baseline nasopharyngeal swabs were obtained from household contacts before the Hajj. However, comparison of the general data and the literature related to the risk of transmission in household contacts of returning pilgrims suggests the transmission of N. meningitidis (12,13). In addition, nasopharyngeal swabs from household contacts of the serogroup B carriers could have provided valuable information about the dominant epidemiologic cause of IMD in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Further, no baseline nasopharyngeal swabs were obtained from household contacts before the Hajj. However, comparison of the general data and the literature related to the risk of transmission in household contacts of returning pilgrims suggests the transmission of N. meningitidis (12,13). In addition, nasopharyngeal swabs from household contacts of the serogroup B carriers could have provided valuable information about the dominant epidemiologic cause of IMD in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Major epidemics of meningococcal meningitis caused primarily by serogroup A have been reported for a number of developing countries (including Brazil, Nepal, China, and several sub-Saharan African nations); attack rates during these epidemics can approach 1% of the population (216,217,255). During an outbreak of invasive meningococcal disease coinciding with the Hajj pilgrimage in March 2000, the attack rate of serogroup W-135 disease was 25 cases per 100,000 population (350). After the Hajj outbreak, serogroup W-135 subsequently spread worldwide and caused a large epidemic of meningococcal meningitis in Burkina Faso in 2002 (85).…”
Section: Neisseria Meningitidismentioning
confidence: 99%
“…Recent studies showed that W-135 and B were the commonest serogroups causing meningococcal meningitis (11,12). The risk of transmission increases owing to the fact that carriage may last between 5 and 15 weeks (13)(14)(15). In the study by Wilder-Smith et al, 15% of pilgrims were carriers of N. meningitidis following their return from pilgrimage, and interestingly 55% of these carriers tested positive during the next 6 months (16).…”
Section: Introductionmentioning
confidence: 99%